Assessment of bacteria-based self-healing concrete through experimental investigations — a sustainable approach - Akula Vishal; Akhilesh Chepuri; N. Chandana (Journal of Materials Science: Materials in Engineering)
Abstract This study aims to evaluate the destructive and non-destructive strength parameters of bacterial concrete with different grades (M20, M25, M30) and cell counts (10^5 and 10^6 cells/ml) using Bacillus subtilis. Additionally, cost analysis and cost–benefit comparisons were conducted for each mix. The effectiveness of B. subtilis in resisting high temperatures was also examined. Findings indicate a 25–40% increase in strength parameters in bacterial concrete compared to conventional concrete. Bacterial mixes consistently showed velocities above 4.45 km/s, indicating excellent quality, surpassing conventional concrete. Notably, bacteria with a cell count of 10^5 cells/ml exhibited greater strength than 10^6 cells/ml across all grades. Cantabro loss tests revealed a 15–25% reduction in wear and tear for bacterial concrete. The bacterial specimens also showed significantly lower strength loss at higher temperatures. This study underscores the potential of bacterial-based self-healing concrete for specific construction applications, offering high temperature resistance, increased strength, and reduced wear and tear.